Gadolinium Contrast Agents for CNS Imaging: Current Concepts and Clinical Evidence - Kanal, E.; Maravilla, K.; Rowley, H.A. (American Journal of Neuroradiology, 2014)
SUMMARY: The aim of this article was to review the properties of the various gadolinium-based contrast agents used for CNS imaging along with the clinical evidence and published data that highlight the impact these different properties can have on diagnostic performance. In addition, approaches to optimizing image acquisition that take into account the different properties of specific gadolinium-based contrast agents and an extensive review of the safety profiles of the various agents are presented. CEcontrast-enhancedCNRcontrast-to-noise ratioGBCAgadolinium-based contrast agentGdgadoliniumNSFnephrogenic systemic fibrosisrCBVrelative cerebral blood volumerCBFrelative cerebral blood flow